Targeted next-generation sequencing for pulmonary infection diagnosis in patients unsuitable for bronchoalveolar lavage - Deng, Zhenfeng; Li, Chunhong; Wang, Yingjin; Wu, Fengwen; Liang, Chunfang; Deng, Wei; Wang, Yuanli (Frontiers in Medicine, 2023)
Background: Targeted next-generation sequencing (tNGS) has emerged as a rapid diagnostic technology for identifying a wide spectrum of pathogens responsible for pulmonary infections.Methods: Sputum samples were collected from patients unable or unwilling to undergo bronchoalveolar lavage. These samples underwent tNGS analysis to diagnose pulmonary infections.Retrospective analysis was performed on clinical data, and the clinical efficacy of tNGS was compared to conventional microbiological tests (CMTs).Results: This study included 209 pediatric and adult patients with confirmed pulmonary infections. tNGS detected 45 potential pathogens, whereas CMTs identified 23 pathogens. The overall microbial detection rate significantly differed between tNGS and CMTs (96.7% vs. 36.8%, P < 0.001). Among the 76 patients with concordant positive results from tNGS and CMTs, 86.8% (66/76) exhibited full or partial agreement. For highly pathogenic and rare/noncolonized microorganisms, tNGS, combined with comprehensive clinical review, directly guided pathogenic diagnosis and antibiotic treatment in 21 patients. This included infections caused by Mycobacterium tuberculosis complex, certain atypical pathogens, Aspergillus, and nontuberculous Mycobacteria. Among the enrolled population, 38.8% (81/209) of patients adjusted their treatment based on tNGS results. Furthermore, tNGS findings unveiled age-specific heterogeneity in pathogen distribution between children and adults.CMTs often fall short in meeting the diagnostic needs of pulmonary infections. This study highlights how tNGS of sputum samples from patients who cannot or will not undergo bronchoalveolar lavage yield valuable insights into potential pathogens, thereby enhancing the diagnosis of pulmonary infections in specific cases.